Investigating the antibacterial activity of sponge extract Callyspongia aerizusa from the waters of Parentek Beach, Lembone East District, Minahasa Regency - Christania Sigarlaki; Defny Silvia Wewengkang; Gerald Edward Rundengan (UNIVERSITAS SAM RATULANGI, 2024)
Callyspongia aerizusa is one type of sponge that grows in the waters of Indonesia, like sponges in general, this species has a porous body and a hard surface like stone. In addition, C. aerizusa can also absorb oxygen from water through the diffusion process. This study aims to determine whether there is antibacterial activity of C. aerizusa sponge extract from Parentek Beach Waters, East Lembean District, Minahasa Regency. This study uses the agar diffusion method (Kirby Bauer diffusion dics) and will see the inhibition zone that will be generated based on its category. Based on the results of the research, C. aerizusa sponge extract has a diameter of inhibition zone produced, namely on Staphylococcus aureus bacteria 8 mm in a concentration of 250 ug and for Eschericia coli bacteria it has no inhibition zone produced